2017
DOI: 10.7150/thno.18614
|View full text |Cite
|
Sign up to set email alerts
|

Bright Polymer Dots Tracking Stem Cell Engraftment and Migration to Injured Mouse Liver

Abstract: Stem cell therapy holds promise for treatment of intractable diseases and injured organs. For clinical translation, it is pivotal to understand the homing, engraftment, and differentiation processes of stem cells in a living body. Here we report near-infrared (NIR) fluorescent semiconductor polymer dots (Pdots) for bright labeling and tracking of human mesenchymal stem cells (MSCs). The Pdots exhibit narrow-band emission at 775 nm with a quantum yield of 22%, among the highest value for various NIR probes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 71 publications
2
44
0
Order By: Relevance
“…Also, the polymer dot-labeled MSCs retained robust self-renewal capacity and multi-lineage differentiation potential. In another study, researchers found that, compared to unlabeled MSCs, cell viability, proliferation and differentiation capacity, tumorigenicity, and immunophenotypic profiles of polymer dot-labeled MSCs also showed no differences 120…”
Section: Nps and Their Toxic Effectsmentioning
confidence: 97%
“…Also, the polymer dot-labeled MSCs retained robust self-renewal capacity and multi-lineage differentiation potential. In another study, researchers found that, compared to unlabeled MSCs, cell viability, proliferation and differentiation capacity, tumorigenicity, and immunophenotypic profiles of polymer dot-labeled MSCs also showed no differences 120…”
Section: Nps and Their Toxic Effectsmentioning
confidence: 97%
“…CPPs can enter cells without causing cytotoxicity at the working does [ 22 ]; therefore, they have been used as a tool for the delivery of various cargoes [ 48 50 ]. Especially in stem cell tracking experiments, CPPs-modified imaging particles did not affect the differentiation potential of stem cells in vitro [ 27 , 51 , 52 ].…”
Section: Advantages Of Cpps In Stem Cell Trackingmentioning
confidence: 99%
“…Although MSCs may form strategic niches in perivascular spaces in almost every region of the body, they migrate to sites of injury for inflammation suppression and wound healing after the detection of local and distant tissue damage [68, 69]. However, the injection of MSCs through the blood vessels leads to the engraftment of MSCs into the lungs and the capillary beds of other tissues or organs, consequently decreasing the number of MSCs migrating to the target areas [70]. RSV pretreatment in a common bile duct ligation (CBDL) animal model improved the therapeutic effects of MSCs via the upregulation of SIRT1 and the downregulation of p53, accompanied by the upregulation of the homing of MSCs to the liver and a decrease in homing of MSCs to the lung and spleen [62].…”
Section: The Effects Of Rsv On Mscs In Vivomentioning
confidence: 99%